Development of Learning Media Pansirbongpas for the Operation of Fraction Numbers for Grade 4 Elementary School - Yasa, Arnelia Dwi; Suastika, I Ketut; Wahyu Ningtyas, Nur Vita (Jurnal Ilmiah Sekolah Dasar, 2020)
The results of the analysis of the learning process show that the teacher does not use attractive learning media and students do not pay attention to the teacher during the lesson. This result in students often experiencing misconceptions about the material of adding fractions, so there is a need for the development of learning media in the form of unloading shading boards that can support the learning process. The purpose of this study was to determine the validity, practicality, and effectiveness. This research method was a development research by adapting the ADDIE model with 5 stages, namely: Analysis, Design, Development, Implementation, and Evaluation. The test subjects in this study were media expert lecturers, material expert lecturers, teachers and fourth grade students of SDN Ngembul 03, Blitar Regency. The data analysis technique used descriptive qualitative and quantitative. The data collection instrument used in this study was a questionnaire. The loading and unloading shading board based on the results of material validation obtained a score of 79.15% in the feasible category, the results of media validation obtained 75% with the feasible category. The results of the validation of the teacher's practicality got 83.65% in the very good category, the results of the student's practicality got 86.66% with the very good category and the results of the student's effectiveness got 81% with the very good category. The unloading shading board can be used by the teacher in the learning process to make it more interesting and fun. Provide a reference for other researchers in developing interesting and fun learning media for loading and unloading shading boards.